The importance of entrainment and bulking on debris flow runout modeling: examples from the Swiss Alps - F. Frank (Natural Hazards and Earth System Sciences, 2015)
This study describes an investigation of channel-bed entrainment of sediment by debris flows. An entrainment model, developed using field data from debris flows at the Illgraben catchment, Switzerland, was incorporated into the existing RAMMS debris-flow model, which solves the 2-D shallow-water equations for granular flows. In the entrainment model, an empirical relationship between maximum shear stress and measured erosion is used to determine the maximum potential erosion depth. Additionally, the average rate of erosion, measured at the same field site, is used to constrain the erosion rate. The model predicts plausible erosion values in comparison with field data from highly erosive debris flow events at the Spreitgraben torrent channel, Switzerland in 2010, without any adjustment to the coefficients in the entrainment model. We find that by including bulking due to entrainment (e.g., by channel erosion) in runout models a more realistic flow pattern is produced than in simulations where entrainment is not included. In detail, simulations without entrainment show more lateral outflow from the channel where it has not been observed in the field. Therefore the entrainment model may be especially useful for practical applications such as hazard analysis and mapping, as well as scientific case studies of erosive debris flows.